Peculiarities of photonic band gap width dependence upon concentration of the admixture layers randomly included in composite material - Rumyantsev, V.V.; Fedorov, S.A.; Shtaerman, E.Ya. (Functional Materials, 2008)
Considered is a model of photonic crystalline superlattice as a set of macroscopically homogeneous layers with randomly included extrinsic (with respect to the ideal superlattice) layers of a variable thickness and composition. The polariton spectrum of such a non-ideal superlattice with an arbitrary number of layers per elementary cell obtained within the virtual crystal method is specified for the Si - diamond crystal system. The peculiarities of the band gap width dependence upon concentration of admixture layers and refractive index are considered. The study carried out shows that optical characteristics of a crystalline superlattice may vary significantly due to transformation of its polariton spectrum caused by the presence of admixture layers.